The Effect of Principal Leadership and Work Motivation on Junior High School Teacher Performance - Dinar Putri Pratiwi; Jumirah Warlizasusi (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2023)
In order to improve the quality of education in schools, not only the role of school principals but also qualified teachers is very influential. The teacher has a duty as a teacher, and more than that, the teacher is an educator and value-adding mentor who guides and guides student learning. For this reason, teachers take an active role and establish themselves as high-performing professionals. Effective principal leadership is created when the principal has good traits, behaviors, and skills to guide school organizations and ultimately achieve good goals and effective quality schools. The aims of this study were (1) the influence of the principal and motivation on the performance of teachers at Rejang Lebong 1 Public Middle School, (2) The influence of the principal's leadership on teacher performance at Rejang Lebong 1 Public Middle School, (3) the effect of work motivation on the performance of teachers of SMP Negeri 1 Lebong Rejang. The population of this study was all teachers at SMP Negeri 1 Rejang Lebong, totaling 65 people. The sampling method adopts a national census. The data analysis technique used is multiple linear regression. The results of this study indicate that (1) principal leadership and work motivation simultaneously have a significant effect on teacher performance, (2) principal leadership has a significant effect on teacher performance, and (3) work motivation has a significant effect. teacher performance at SMP Negeri 1 Rejang Lebong.